Financial Inclusion as Enabler for Innovation in Banking - Beatriz Fernández-Olit; Gloria González-Sanz; Óscar Sierra-Martín; Elena Ortega-Diaz (Foresight and STI Governance)
Using evidence from Spain, this study assesses the readiness of the banking sector of the EU to introduce technological and social innovations to implement the European policy of financial inclusivity. Despite the evident benefits for banks in terms of enhancing legitimacy and improving consumer knowledge and loyalty, mostly banks at present merely comply with the formal aspects of financial inclusion regulation, but are not going further in terms of technical or social innovation, using compliance to avoid the "stick" of regulation. In contrast, a review of the banks’ own corporate social responsibility strategies shows a higher level of commitment and innovation in terms of financial inclusion. Based on the analysis of institutional factors that determine the involvement of banks in the inclusivity policy, recommendations are proposed for adjusting development strategies in order to combine the efforts of the public and private sectors in the provision of public services.